Research Paper: Investigating The Power Conversion Efficiency of Perovskite Solar Cells with The Inorganic Active Layer RbGeBr3 and Various Electron and Hole Collecting Layers - Shima Valizadeh; Ali Asghar Shokri; Amir Abbas Sabouri Dodaran (فیزیک کاربردی ایران, 2023)
Perovskite solar cells (PSCs) are advancing swiftly due to their remarkable increase in power conversion efficiency (PCE) compared to traditional photovoltaic technologies. The main purpose of this study is to investigate the efficiency of two distinct PSCS structures that use  as an inorganic perovskite active layer. The calculations are based on the optoelectronic model of the solar cell and the use of the finite element method to solve the continuity equations for current and charge density. Therefore, the layer thicknesses of different materials (as ETL and Active layer) are modified to find the better power conversion efficiency of these solar cells. The obtained results of simulation calculations illustrate that the first structure FTO/ITO/  /PEDOT: PSS/Au exhibits a maximum power conversion efficiency of 11.37%, with a short circuit current of 14.47 (mA/cm^2) and an open circuit voltage of 0.96 (V) and while the FTO/TiO2/ /Spiro- OMETAD/Au structure shows a maximum power conversion efficiency of 10.57%. The greatest power conversion efficiency for the aforementioned designs is 80 nm for the electron transporting layer is 80 nm and 200 nm for the inorganic active layer, respectively. The results of this article can be useful in the design of new-generation solar cells based on inorganic perovskite layers.